Triple fixed-dose combination of amlodipine, indapamide and perindopril for hypertension in patients with stable coronary artery disease and abdominal obesity - E. A. Polyakova; Yu. Sh. Khalimov (Российский кардиологический журнал)
Aim. In an open-label clinical trial, to evaluate the effectiveness and impact on metabolic parameters of triple antihypertensive combination therapy with amlodipine, indapamide and perindopril arginine (perindopril A) in patients with hypertension (HTN) and stable coronary artery disease (CAD) in combination with abdominal obesity (AO), who have not had an adequate response to dual antihypertensive therapy for at least 4 weeks.Material and methods. The study included 68 adult patients aged 42 to 64 years (51 (47; 60) years) with AO, stable CAD and uncontrolled HTN, despite treatment with two drugs: an angiotensin-converting enzyme (ACE) inhibitor and a thiazide and thiazide-like diuretic. In the study, patients, in accordance with the general characteristics of the drug, after prescribing a free triple-dose combination of amlodipine, indapamide, perindopril in appropriate dosages, received one of the following combination of amlodipine/indapamide/perindopril for 24 weeks: group 1 (n=34) — 10/2,5/10 mg and group 2 (n=34) — 5/1,25/5 mg, one tablet daily. The analysis of the primary endpoint was to assess the change in mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) in the sitting position from baseline to 24 weeks. Secondary efficacy endpoints included the proportion of patients achieving target mean SBP and DBP values for this category in the sitting position of 120-130 mm Hg and 70-79 mm Hg, respectively, at 12, 16, 20 and 24 weeks. Safety was assessed throughout the study. The effect on metabolic parameters was assessed at 24 weeks of the study.Results. Sixty-seven (98,5%) patients completed the study. The mean decrease in blood pressure from the initial level (group 1159/96 mm Hg; group 2161/95 mm Hg) to 24 weeks (group 1 126/76 mm Hg; group 2 132/84 mm Hg) was significant (p<0,0001 for all). The proportion of patients who reached the target mean values of SBP (120-130 mm Hg) and DBP (70-79 mm Hg) in the sitting position by 24 weeks was 80,16% and 79,28% in group 1, respectively; in group 2 — 65,32% and 70,06%, respectively. No serious adverse events were recorded. Its administration, regardless of the doses of individual components in combination, was accompanied not only by metabolic neutrality in relation to carbohydrate, lipid and purine metabolism, a decrease in chronic inflammation, but was also associated with a decrease in serum leptin concentration and subcutaneous adipose tissue, an increase in tissue sensitivity to leptin, as well as a decrease in the size of adipocytes in subcutaneous fat.Conclusion. Triple fixed-dose of amlodipine/indapamide/perindopril in two different dosages is effective, safe and well tolerated in patients with HTN and stable CAD in combination with AO.